Pemanfaatan Teknologi Media Pembelajaran oleh Guru di SDIT Bunayya pada Masa Pandemi Covid-19 - Nirmalasari, Endah; Weni, Mustika; Ramadhinia, Nadya; Amelia, Rosa (ANWARUL, 2022)
This study aims to determine the use of online learning technology during the Covid-19 virus pandemic which has spread throughout the world, especially Indonesia using the google classroom, YouTube, WAG, Edmodo, Zoom, and Googlemeet platforms. The research we conducted used a qualitative approach by collecting data with several methods that we did in writing this article. We use the interview method, literature study and literature, then the results show that technology has many roles and benefits in the world of education, especially during distance learning in the midst of the Covid-19 pandemic. By conducting interviews with teachers and students, it can be concluded that the learning media technology that is widely used by elementary schools is WAG and also google classroom.